Creation of an algorithm for forming the stages of the technological process for manufacturing blanks for blockboards from post-consumer wood - Medvid , Lyubomyr (Forestry, Forest, Paper and Woodworking Industry, 2025)
The problem of rational use of post-consumer wood (PCW) is considered by creating an algorithm for forming the stages of the technological process for manufacturing blockboard of various designs, which is based on a phased analysis and modeling of technological operations. A general structural scheme for processing used wood is proposed, covering all the main technological links - from material collection to the formation of finished boards, which allows rationalizing the production process and reducing material losses. Modeling of technological solutions has proven the effectiveness of a phased approach to processing used wood, especially taking into account its heterogeneity, pollution and damage. It is substantiated that the most realistic and practically applicable approach to solving the sorting problem is the analysis (of the volumes of accumulation of waste wood for material or energy use), the volumes of waste wood by the amount of contamination (sorting by categories), the volumes of waste wood by dimensional suitability (to obtain specification blanks) and the description of the procedure for making current decisions about sufficient volumes of waste wood. Methods of surface cleaning of waste wood are proposed, in particular. a mechanized method using a needle milling tool. The production of dimensionally suitable blanks from used wood is a key stage that ensures stable quality of finished joinery products and increases the efficiency of using secondary raw materials. A typical workshop plan has been developed, which provides for sorting of waste wood by four categories, by type of material - solid wood, board; by removing metal inclusions and other contaminants. The basis of the workshop are through-type machines for performing surface longitudinal cleaning operations. In particular, for PCW-I, a four-sided grinding machine is used, for PCW-II – a two-sided grinding machine, for PCW-III – a two-sided needle milling machine, for PCW-IV – a four-sided needle milling machine. This approach helps to optimize production processes, increase the efficiency of material processing and reduce wood waste. PCW prepared according to such stages and recommendations is an additional raw material for the production of blockboard and other structural materials.